Integrasi Tri Pusat Pendidikan dalam Pendidikan Agama Islam - Samsudin Samsudin (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
Abstract: In globalization epoch met by many big influence to society. Influence of good terebut not all but there is also negative influence. Education of Islam as one of the stock to realize real moslem. At its execution of education of application Islam have to pass three education center. Three the education center cover family, society and school. In conducting this research, researcher use research type qualitative. So that the following research mengasilkan: (1) Three education center is three education center covering family, society and school. Third of the environment have responsibility and duty in educating nation child. Family, society and school as underwriter of answer education which must always work along harmoniously. From third the education environment will fall to pieces do not walk one way otherwise keep together. (2) Third education environment as place inculcate Islam teaching values having a purpose to form child become person which either through spirit and also bodily. Family as cultivation first time about Islam teaching, go to school as medium to develop and society as medium for the application of it. (3) Education of Islam represent one of the good stock of life of and also world of eternity. So that execution of process education of Islam must be done pass three education center. Role of family, compact society and school will have strong influence in creating human resource which is genius, high with quality and have august personality